Efficient Key Management for Data Security using TDES - Puri, Gaurav (My University, 2015)
Data security is the prime requirement for all the organizations in order to keep their important information safe from the hacker. Encryption is process of converting plaintext into cipher text. The strength of this cryptographic technique comes from the fact that no one can read the information without altering its content. There are various techniques which are used to keep the data confidential from hacker; these are passwords, cryptography and biometrics. The passwords are not so good for this task due to their low entropy and Biometrics is too costly and sometimes this technique also produces harmful effects to the human beings. Cryptography is the best solution for the above problem. In this report comparative study of various encryption algorithms has been done. From the Literature Survey; various observations and gaps have also been shown. Objectives have also been derived from the observations and gaps. Using dynamic keys simulation results have been achieve using MATLAB 2013. Finally, comparison of our approach with existing algorithms has also been done in terms of encryption and decryption time.
M.E. (ECED)
Keywords: Encryption; ECED